Windows 2000 configuration wizards - Collins, Brian M.; Cunningham, Stace; Weiss, Martin; Shields, Paul. (Rockland, MA : Syngress Media, 2000)
Developers are used to working with Wizards, component-like products that allow them to create certain elements - like dialog buttons - quickly and easily while they are coding applications. With the launch of Windows 2000, Microsoft has announced a new set of Wizards that will help administrators and users configure and set up Windows 2000 Professional (the Windows NT 4 Workstation successor) and Windows 2000 Server (the Windows NT 4 Server successor). Windows 2000 Setup and Configuration Wizards covers all the available Wizards, with an emphasis on those new to Windows 2000. Each Wizard is broken down by dialog box, with explanations of all options and required elements so administrators will know what to be prepared with. In addition, coverage of new services that will speed configuration and set up (like the Windows Installer) will be covered. * This is the first book to focus on Wizards and Windows 2000 automated components * Network administrators and developers will save time using this book.
Preinstallation--Windows 2000 setup wizard--Configuring Windows 2000--Active directory installation wizard--Managing DHCP servers--Create a new zone wizard (DNS)--Routing and remote access configuration wizard--Create shared folder wizard--Add printer wizard--Internet Information Services (IIS) wizards--Windows component wizard--Windows 2000 resource kit setup wizard--Add/remove hardware wizard--Internet connection wizard--Connection manager administration kit wizard--Create new Dfs root wizard--Delegation of control wizard--Create partition wizard--System maintenance wizards--Environment configuration wizards--Accessibility wizard--Send FAX wizard--Backup and recovery wizards--Microsoft Windows 2000 registration wizard--Index.
Includes index.
Keywords: Microsoft Windows (Computer file).; Operating systems (Computers).; Computer network; Internetworking (Telecommunications); Microsoft Windows 2000 (Computer file); Electronic books